Biometric Voting Integrated with Islamic Political Principles: to Enhance Democracy in Bangladesh's E-Voting System - Mohammad Eisa Ruhullah; Thameem Ushama (Istinbath : Jurnal Hukum, 2024)
This paper addresses the vital importance of fair and transparent elections as the foundation of a robust democracy, crucial for representing citizens' voices and fostering trust in the electoral process. In Bangladesh, the pursuit of fair elections faces significant challenges, including transparency issues, accountability concerns, and instances of voter fraud. This analysis presents a novel approach that combines Quranic principles with biometric voting technology to address the challenges faced by the current voting system. Taking inspiration from Islamic values, particularly those that emphasize justice, equality, and accountability, the proposed framework intends to improve the democratic aspect of e-voting in Bangladesh. By incorporating biometric authentication mechanisms, such as fingerprint or iris scanning, this framework seeks to ensure the integrity of the voting process while adhering to Quranic and Prophetic principles of fairness and transparency. This study explores the feasibility and implications of implementing such a system within Bangladesh's electoral landscape through a multidisciplinary approach that bridges Islamic scholarship, technological innovation, and political theory. By leveraging the potential of biometric voting technology guided by Quranic principles, this research contributes to the ongoing discourse on electoral reform and democratization in Bangladesh, offering valuable insights into how technology and ethical considerations can intersect to strengthen democratic governance.